Dampak Kurangnya Fasilitas Terhadap Proses Belajar Mengajar Di Sekolah Luar Biasa Swasta (SLBS) Al-Halim - Ayu, Ayu; La ode Abdul Habib Kadir; Reza Faizal Suhaimin; Nurul Wahyuni; Izla Swasty; Haliadi, Haliadi (Journal of Humanities, Social Sciences, and Education, 2026)
Education is a basic right of every citizen, including children with special needs (ABK) who require special education services to develop their potential optimally. One important factor in supporting successful learning is the availability of educational facilities and infrastructure, however, in reality, there are still special schools with limited facilities. This study aims to analyze the impact of the lack of facilities on the teaching and learning process at the Al Halim Private Special Needs School (SBLS). The study used a descriptive qualitative approach. Data collection was conducted through observation, interviews, and documentation on November 21, 2025. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results show that limited classroom space, a lack of learning media, and a lack of supporting facilities have an impact on the suboptimal implementation of learning and individual services for students according to their special needs. These conditions limit the variety of learning methods that can be applied by teachers. However, the availability of dormitory facilities and free shuttle services are supporting factors for the continuity of student education. This study has limitations in the number of subjects and the scope of the study. Therefore, support from schools and the government is needed to improve facilities and infrastructure to enhance the quality of education for children with special needs.